The epidemiology of head, neck and face injuries of adult men`s and women`s U.S. rugby-7s players - Ma, S.-Y. R.; Victoria, C.; Ompad, D. C.; Weinstein, M. G.; Cantu, R. C.; Genece, J.; Allen, A. A.; Lopez, V. (British Journal of Sports Medicine, 2021)
Background Head and neck injuries are a collision sport concern, however there is a lack of Rugby-7s injury data, particularly in emerging Rugby nations.